2000
DOI: 10.1152/ajpheart.2000.278.4.h1256
|View full text |Cite
|
Sign up to set email alerts
|

Detection of low- and high-frequency rhythms in the variability of skin sympathetic nerve activity

Abstract: Spectral analysis of skin blood flow has demonstrated low-frequency (LF, 0.03-0.15 Hz) and high-frequency (HF, 0.15-0.40 Hz) oscillations, similar to oscillations in R-R interval, systolic pressure, and muscle sympathetic nerve activity (MSNA). It is not known whether the oscillatory profile of skin blood flow is secondary to oscillations in arterial pressure or to oscillations in skin sympathetic nerve activity (SSNA). MSNA and SSNA differ markedly with regard to control mechanisms and morphology. MSNA contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 25 publications
(38 reference statements)
1
24
0
1
Order By: Relevance
“…In all thermal conditions, data were subdivided into 1,024-point segments (128 s) with 50% overlap, windowed (Hanning method), transformed, and averaged. For consistency with previous studies (2,5), the LF (0.03-to 0.15-Hz) and HF (0.15-to 0.45-Hz) spectral powers of SSNA were calculated from the autospectra. Because the present results showed that spectral power of integrated SSNA can be Ͼ0.45 Hz but Ͻ2.5 Hz, we calculated the spectral power between 0.45 and 2.5 Hz and termed this the veryhigh-frequency (VHF) component.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In all thermal conditions, data were subdivided into 1,024-point segments (128 s) with 50% overlap, windowed (Hanning method), transformed, and averaged. For consistency with previous studies (2,5), the LF (0.03-to 0.15-Hz) and HF (0.15-to 0.45-Hz) spectral powers of SSNA were calculated from the autospectra. Because the present results showed that spectral power of integrated SSNA can be Ͼ0.45 Hz but Ͻ2.5 Hz, we calculated the spectral power between 0.45 and 2.5 Hz and termed this the veryhigh-frequency (VHF) component.…”
Section: Discussionmentioning
confidence: 92%
“…Respiratory rhythms in integrated SSNA (1) and in single vasoconstrictor and sudomotor neurons (13) were verified using interval histogram analytic techniques. Using spectral analysis of integrated SSNA, Cogliati et al (2) showed that SSNA during normothermia had a high-frequency (HF) oscillatory component, which reflected the respiratory rhythm. Moreover, they reported that SSNA also had a low-frequency (LF, 0.1-Hz) oscillatory component, which was coherent with LF components of R-R interval and blood pressure (2).…”
mentioning
confidence: 99%
“…Studies that investigated the relationship between more direct measures of sympathetic nerve firing and HRV produced conflicting results. Although some reports found no significant correlation between changes in cardiac or muscle sympathetic nerve activity (MSNA) and changes in LF R-R interval power (20,26), others reported that spectral analysis of MSNA and R-R interval variability share almost identical oscillatory components with a high correlation between both measures in the human subject (9,36,38,50). LF R-R interval oscillations may also be related to cardiac sympathetic modulation resulting from the baroreflex response to LF BP oscillations (8).…”
Section: Interpretation Of Changes In Hrvmentioning
confidence: 99%
“…Resolution of these questions will require invasive arteriovenous studies of different adipose tissue depots and further studies of in vitro oscillations with and without stimulation by sympathetic agonists. Cyclicity is a characteristic shared by a variety of systems that are under control of the sympathetic nervous system, such as oscillations of skin sympathetic nerve activity (47) and sympathetic nerve discharge by central neurons (48). The activity of the sympathetic nervous system is directly influenced by the CNS (13), which plays an important role as the control center of energy homeostasis (9,49).…”
mentioning
confidence: 99%